Collaborative Capacity Organizations in Handling Stunting in Southwest Papua Province - Anhar Akib Kadar; Muh. Akmal Ibrahim; Hasniati Hasniati; Didik Iskandar (Journal Social Civilecial, 2025)
Stunting remains a major public health challenge in Indonesia, particularly in Southwest Papua Province, where geographical constraints and institutional limitations hinder the implementation of integrated intervention programs. This study examines the organizational collaborative capacity of the Stunting Reduction Acceleration Team (TPPS) in Southwest Papua using Lai's Organizational Collaborative Capacity framework. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and document analysis involving representatives from Bappeda, the Provincial Health Office, the Food Security Office, the Government Bureau, Posyandu cadres, community leaders, religious leaders, and non-governmental organizations. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that while organizational dependency among stakeholders is strong, active participation remains uneven across institutions. Resource disparities, fragmented information exchange, and limited collaborative learning continue to constrain the effectiveness of cross-sector collaboration. The study also reveals that geographical isolation intensifies organizational dependency and creates additional barriers to integrated service delivery. These findings extend Lai's framework by highlighting the influence of geographical complexity on organizational collaborative capacity in decentralized public health governance. Strengthening institutional collaboration requires more equitable resource allocation, integrated information systems, continuous inter-organizational learning, and greater substantive participation among collaborative actors to improve the sustainability of stunting reduction programs.